High-sensitivity pressure sensor using a polymer-embedded FBG - Ahmad, Harith; Harun, Sulaiman Wadi; Chong, Wu Yi; Zulkifli, Mohd Zamani; Thant, Muang Muang Myo; Yusof, Zainun; Poopalan, Prabakaran (John Wiley & Sons, 2007)
A new pressure sensor based on fiber Bragg gratings (FBG), is described with high-pressure sensitivity. The sensor is configured by embedding the FBG in a polymer-field aluminum casing with an opening on one side, which is exposed to pressure measurand. The measured pressure response is 0.06 nm/psi that is ∼2700 times higher than the pressure response measured with a bare FBG. The linearity of the designed sensor is also shown to be good at pressures below 50 psi. This sensor has numerous potential applications in the area of low-pressure measurements.